Green synthesis of nano silver on TiO2 catalyst for application in oxidation of thiophene. (18th May 2019) - Saha, Biswajit; Kumar, Suman; Sengupta, Sonali
Highlights: Preparation of nano-Ag/TiO2 catalyst from silver nitrate and Tulsi leaf extract. Characterisation and application of Ag/TiO2 catalyst in thiophene oxidation. Both pseudo-homogeneous and heterogeneous rate models are proposed. Endothermicity of the reaction was established by thermodynamic analysis. Surface reaction is found to be the rate limiting step following L-H kinetic model. Abstract: The present research work describes the preparation of silver nanoparticles from silver nitrate, and Tulsi (Ocimum tenuiflorum) leaf extract, impregnation on titanium dioxide (TiO2 ) and evaluation of the catalytic activity of this nano silver impregnated TiO2 in the oxidation reaction of thiophene. Tertiary-butyl hydroperoxide was used as an oxidant in the reaction. The catalyst was characterized by BET, SEM, XRF, TEM, UV–Vis spectroscopy, XPS and TPR. The effect of process parameters such as speed of agitation, catalyst weight, oxidant to sulfur mole ratio, silver loading in the catalyst and temperature on the oxidation reaction was studied. Both pseudo-homogeneous and heterogeneous kinetic models were considered and applied for the result. The pseudo-homogeneous form of rate equation shows the reaction follows second order kinetics and is endothermic. Langmuir-Hinshelwood kinetic model is proposed, considering the reaction as a heterogeneous one with solid catalyst and found that surface reaction is the rate controlling step. This model is well fitted with experimental data.